Editorial Introduction: Migration Dynamics, Trajectories and Policies in the Context of Russian Full-Scale Aggression against Ukraine - Marta Jaroszewicz; Oksana Mikhaieva (Central and Eastern European Migration Review, 2024)
This editorial introduction sets the scene for the second part of the Special Section devoted to studying the multi-faceted migration-related consequences of the Russian full-scale invasion against Ukraine of 24 February 2022. Different kinds of migration, migration policies, practices of assistance and solidarity and also experiences of discrimination and exclusion happening in the aftermath or in the context of the Russian aggression against Ukraine after 24 February 2022 – whether inside Ukraine, in neighbouring states or globally – remain within the scope of both parts of this Special Section, with the first part having been published in June 2023.